Comparison between incidental malignant and benign breast lesions detected by computed tomography: A systematic review. Issue 5 (26th March 2013) - Bach, Andreas Gunter; Abbas, Jasmin; Jasaabuu, Cholpan; Schramm, Dominik; Wienke, Andreas; Surov, Alexey
Abstract Introduction With increasing use of CT for a variety of diagnostic pathways, breast incidentalomas will be identified more frequently. Therefore, it is important for radiologists to know typical CT appearances of malignant and benign breast lesions. The aim of this study was to compare radiological features of benign and malignant incidental breast findings on CT reported in the literature. Methods A search for appropriate studies published between 1988 and 2012 yielded five results with a total of 214 patients/257 lesions. Morphological features of the described breast masses, such as shape, margins, enhancement, axillary lymphadenopathy and calcifications, were analysed. Results The prevalence of incidental breast carcinoma varied from 9.2% to 60.9% of the lesions. The frequency of benign lesions was 30.4–71.8%. The remaining incidental findings were intramammary metastases and primary or secondary breast lymphomas. Malignant lesions were larger in size, were round in shape and demonstrated a higher density compared with benign lesions. There was no significant difference in the margin characteristics of the masses between the groups. The morphological features previously postulated as typical for malignancy turned out to be non‐specific. Conclusions Benign and malign breast incidentalomas are not safely distinguished from each other on standard chest CT. Therefore, all breast incidentalomas should be evaluated by further radiological/histological investigations.